Land reclamation without using soil-fills - Yeo, Eng Swee (2016)
Singapore has been developing rapidly over the past decades. In order to sustain the fast-paced economic development and urbanisation, an increasing emphasis has been placed on land reclamation projects. Coupled with inflation and increasing cost of fill materials, conventional land reclamation methods are slowly becoming less feasible due to the increasing cost. An ideal solution is the use of non-soil fill reclamation method which will eliminate the use of such fill. Before reclamation using non-soil fill technique can be carried out, feasibility of the method is first investigated. The retaining wall structure constructed must be able to bear the lateral loading of 10 m to 20 m of seawater level.